2022
DOI: 10.1051/0004-6361/202141570
|View full text |Cite
|
Sign up to set email alerts
|

Stellar labels for hot stars from low-resolution spectra

Abstract: We set out to determine stellar labels from low-resolution survey spectra of hot stars, specifically OBA stars with Teff ≳ 7500 K. This fills a gap in the scientific analysis of large spectroscopic stellar surveys such as LAMOST, which offers spectra for millions of stars at R ~ 1800 and covers 3800 Å ≤ λ ≤ 9000 Å. We first explore the theoretical information content of such spectra to determine stellar labels via the Cramér-Rao bound. We show that in the limit of perfect model spectra and observed spectra wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 130 publications
2
48
0
Order By: Relevance
“…The importance of B-type supergiants in this context lies in their large luminosities, so that sight lines to very distant parts of the Milky Way may become traceable in the era of large spectroscopic surveys (e.g. Xiang et al 2022). A comparison with stellar evolution models then also allows the fundamental parameters to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of B-type supergiants in this context lies in their large luminosities, so that sight lines to very distant parts of the Milky Way may become traceable in the era of large spectroscopic surveys (e.g. Xiang et al 2022). A comparison with stellar evolution models then also allows the fundamental parameters to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hawkins (2022) mapped azimuthal variations in the Galactic disc, using both Gaia DR3 data and sample OBAFtype stars from the LAMOST survey published by Xiang et al (2022). Using the LAMOST sample, the author found an azimuthal structure on top of the radial gradient, which does not necessarily follow the spiral arms.…”
Section: Discussionmentioning
confidence: 99%
“…8). In their recent study of OBA-type stars in the LAMOST survey, Xiang et al (2022) demonstrated that the impact of NLTE effects on the spectroscopically inferred T eff values is negligible for stars cooler than 25 000 K. In particular, the authors showed an overall good consistency between the Kurucz LTE and Potsdam Wolf-Rayet (PoWR; Hainich et al 2019) NLTE models at T eff 25 000 K (their Figs. C.1 and C.2), and reported a good agreement between the parameters obtained with the LTE and NLTE models for stars below that same T eff cut-off value (their Fig.…”
Section: Spectrum Analysis With Zeta-paynementioning
confidence: 96%